Validity and Psychometric Evaluation of the Chinese Version of the 5-Item WHO Well-Being Index - Sai-fu Fung; Chris Yiu Wah Kong; Yi-man Liu; Yi-man Liu; Qian Huang; Zike Xiong; Zhiquan Jiang; Fangfang Zhu; Zhenting Chen; Kun Sun; Huiqin Zhao; Ping Yu; et al. (Frontiers Media S.A., 2022)
AimsThis article evaluates the psychometric properties of the Chinese version of the 5-item WHO Well-Being Index (WHO-5) in mainland China.MethodsTwo cross-sectional studies with 1,414 participants from a university in China were conducted. The Chinese version of the WHO-5 was assessed to determine its internal consistency, concurrent validity, factorial validity, and construct validity.ResultsThe results indicate that the WHO-5 is unidimensional and has good internal consistency, with Cronbach's a = 0.85 and 0.81 in Study 1 (n = 903) and Study 2 (n = 511), respectively. The findings also demonstrate that the WHO-5 has good concurrent validity with other well-established measures of wellbeing, self-efficacy, self-esteem, and mental wellbeing. The results of confirmatory factor analysis also suggest that the scale has a good model fit.ConclusionsThis study provides empirical data demonstrating that the Chinese version of the WHO-5 has good psychometric properties. The scale can be a useful measure in epistemological studies and clinical research related to wellbeing in Chinese populations.